2023
DOI: 10.18063/ijb.v9i2.662
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on repair of cartilage defects in the rabbits with GelMA-MSCs scaffold prepared by three-dimensional bioprinting

Abstract: Cartilage damage is a common orthopedic disease, which can be caused by sports injury, obesity, joint wear, and aging, and cannot be repaired by itself. Surgical autologous osteochondral grafting is often required in deep osteochondral lesions to avoid the later progression of osteoarthritis. In this study, we fabricated a gelatin methacryloyl-marrow mesenchymal stem cells (GelMA-MSCs) scaffold by three-dimensional (3D) bioprinting. This bioink is capable of fast gel photocuring and spontaneous covalent cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…82 A low concentration (5%) of GelMA was more favorable for MSC chondrogenic differentiation than a high concentration (10%). 77 SilMA has high porosity, but its pore size is small; the average pore size of SilMA is 2.29 ± 0.77 μm 2 . 60 The pore size of MAC ranged from 5 to 25 μm 2 , and it was increased when the concentration of CH decreased.…”
Section: Mechanical Properties and Effect On Cellmentioning
confidence: 96%
See 3 more Smart Citations
“…82 A low concentration (5%) of GelMA was more favorable for MSC chondrogenic differentiation than a high concentration (10%). 77 SilMA has high porosity, but its pore size is small; the average pore size of SilMA is 2.29 ± 0.77 μm 2 . 60 The pore size of MAC ranged from 5 to 25 μm 2 , and it was increased when the concentration of CH decreased.…”
Section: Mechanical Properties and Effect On Cellmentioning
confidence: 96%
“…54 However, when the concentration of polymer was too high (for example, the concentration of GelMA >10%), the high concentration polymer could form a denser cross-linked network inside the hydrogel, which would limit cell growth and migration. 77 The mechanical properties of hydrogels are key factors in determining suitable conditions for stem cell differentiation. Li et al reported an enhancement in the osteogenic and chondrogenic differentiation abilities of BMSCs with increasing viscoelasticity.…”
Section: Mechanical Properties and Effect On Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the cell source, when using stem cells in co-culture with CCs or in mono-culture, most of the papers report positive outcomes in cartilage formation when using BMSCs in 3D bioprinted constructs implanted in subcutaneous mouse models and in orthotopic rabbit models [ 68 – 71 , 73 – 75 ]. As an alternative, Di Bella et al [ 76 ] used adipose-derived stem cells (ADSCs) isolated from the infra-patellar fat pad in a pilot study based on the orthotopic implantation in sheep.…”
Section: In Vivo Advances In the 3d Bioprinting Of Cartilagementioning
confidence: 99%